2022
DOI: 10.1101/2022.01.29.478309
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of 3D breast cancer models with human T cells expressing engineered MAIT cell receptors

Abstract: Immunotherapy has revolutionized cancer treatment with the advent of advanced cell engineering techniques aimed at targeted therapy with reduced systemic toxicity. However, understanding the underlying immune-cancer interactions require development of advanced three-dimensional (3D) models of human tissues. In this study, we developed proof-of-concept 3D tumor models with increasing complexity to study the cytotoxic responses of CD8+ T cells, genetically engineered to express mucosal-associated invariant T (MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Discrepancies in MR1 expression across various tumor cell lines and the resulting differences in MAIT cell response underscore the complexity of the immune system’s interaction with cancer. Utilization of 3D bioprinted tumor models to study the effect of localization and activation of MAIT cells within the 3D tumor tissue model could help elucidate and these complex interactions ( 99 ).…”
Section: Role Of Mait Cells In Cancer Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Discrepancies in MR1 expression across various tumor cell lines and the resulting differences in MAIT cell response underscore the complexity of the immune system’s interaction with cancer. Utilization of 3D bioprinted tumor models to study the effect of localization and activation of MAIT cells within the 3D tumor tissue model could help elucidate and these complex interactions ( 99 ).…”
Section: Role Of Mait Cells In Cancer Treatmentmentioning
confidence: 99%
“…Furthermore, several studies demonstrated the potential for MAIT cells in solid tumor-targeting immunotherapies due to their natural ability to infiltrate tissue sites of chronic inflammation and their abundance in the tumor microenvironment ( 99 , 101 , 109 , 110 ). In this tumor environment, MAIT cells can also act as innate T cells with the potential to bridge innate and adaptive immune immunity, and can rapidly exert their effector functions upon activation without the requirement for clonal expansion, similar to innate immune ( 111 ) ( 112 ).…”
Section: Role Of Mait Cells In Cancer Treatmentmentioning
confidence: 99%
“…RNAseq analysis supported their hypothesis that the bioprinted model better mimicked the physiological environment (Figure 2C). To create a tumorimmune interaction model, Dey et al printed a ring of T cells into a collagen bath and deposited a single MDA-MB-231/human dermal fibroblast spheroid in the center (Figure 2D) (73). In each of the print designs, cancer cells migrated from the central spheroid and invaded into the collagen matrix.…”
Section: D Bioprintingmentioning
confidence: 99%